219k views
3 votes
Simplify using PEMDAS
5+6•3-1

User Jfmatt
by
5.5k points

2 Answers

3 votes

Answer:

22

Explanation:

P E M D A S = Parentheses, exponents, multiplycation, division, addition, and subtraction.

In the problem, it says: 5 + 6 • 3 - 1

In PEMDAS, multiplycation goes first, so 6 • 3 = 18, then addition because it is sooner in the problem, so 18 + 5 = 23 - 1 = 22.

User SomethingDark
by
4.8k points
6 votes

Answer:

22

Explanation:

PEMDAS

P-Parentheses

E-Exponents

M-Multiplication

D-Divison

A-Addition

S-Subtraction

5+6•3-1

(6•3=18)

(5+18=23)

23-1=22

User Rwilliams
by
4.5k points